Symposium 13: Net-wiring the Learning Environments to address Emerging Organisational Needs - Protogeros, Nicolaos (Proceedings of the International Conference on Networked Learning, 2008)
The shift from the industrial economy to the information economy that has happened over the years has led to an enormous increase in competitiveness among organisations. This in turn has led to the development of information technology to highly advanced levels. It is now able to support modern enterprise operation in extremely intricate environments where the changing needs of the business community forces firms to be more agile and responsive. The development of technologies that can efficiently handle complex information such as software agents, combined with the development of Internet technologies for learning process integration and automation such as Web Services, is causing considerable impact on the way economic actors and their roles are implemented in the worldwide market place. This technological evolution has lead to the development of the new value-creating economic paradigm of e-learning, which can exhibit its full potential if approached with modern tools such as the Living Labs methodology. The network based Information economy and the virtual-yet-real learning environments are a promising reality. New theories and technologies such as Software Agent and Web-Services can be applied to customize learning service provision and support distant formation and operation, to plan requirements for Collaborative Learning, and to share Active Learn-ware and Learner-generated content. They are mature and flexible, forming a concrete framework for successful operation of learning environments. At the same time, serious challenges to the future effectiveness of these environments are also sensed and discussed throughout our paper. Two main dimensions can be identified in this context: The Web service dimension - a very popular technology for learning environments integration and operation where the academic approach hasn’t solved the fundamental problems of selecting the most appropriate learning service and coping with learning service discovery as yet. How do interested parties find the learning style and content they’re looking for? How do they advertise? How can software do this on behalf (but without the intervention) of a person? Many proposals along these lines exist, ranging from content-based routing in the early 1990s to the use of DAML-S for agents in recent years but none of them has led to deployed, practical learning systems so far. The Software agent dimension - this includes Multi Agent Systems (MAS) technology, Mobile Agents, Intelligent Agents and other combinations of traditional agent technologies to support parts of the learning interactions (mainly) at the transactional level. The aim of our paper is to discuss the main issues, trends and opportunities related to the application of agent and Web service technologies to networked learning environments, from the above-mentioned dimensions. The paper will take a comprehensive approach, and present practical solutions to promote the adoption of the Living Labs methodology for tackling with all different levels of the networked learning uptake and deployment process. Our paper concludes with a discussion of the business integration requirements in the modern enterprise environment and other emerging inter-organizational models as well as the presentation of relevant and recent developments and solutions (both academic and industrial) addressing the several dimensions and issues of the addressed field.